Theoretical and methodological aspects of the recreation activity in Ukraine - Ridei, Nataliia; Khitrenko, Tetiana; Pavliv, Alona; Khitrenko, Volodymyr (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The analysis concepts and categorical apparatus of recreation in Ukraine on legal, reference, scientific and methodical literature sources are made. It is determined the features of structural organization of recreation sphere, the state and prospects of its development. The structural and organizational scheme of conceptual-categorical apparatus of recreation has been developed. There were clarified existing approaches and classification features based on the developed classifications and suggested author’s approaches, features and species.
Keywords: recreation; recreational territories agrosphere; environmental control; legal regulation; rural green tourism